Marketing Strategy At Mitra Terang Bojonegoro Gold Shop Using SWOT Analysis To Increase Sales Omzet - Cahya Gutama Putra; Siti Ning Farida (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Mitra Terang Bojonegoro Gold Shop is a business engaged in the retail sector of gold-based jewelry which is traded to the public as a research motorcycle taxi. The purpose of this study was to determine the marketing strategy of Mitra Terang Bojonegoro Gold Shop to increase sales turnover. The method of this study uses a qualitative descriptive method assisted by the SWOT analysis method. In collecting data, the technique used is through in-depth interviews, participating observation, and documentation related to the 4P marketing mix (product, price, promotion, place). This is useful for identifying strengths, weaknesses, opportunities and threats with the SWOT analysis method at Mitra Terang Bojonegoro Gold Shop. Based on this study, the results of IFAS and EFAS showed strength with a score of 3.0 and weakness with a score of 2.25. Then, it shows an opportunity with a score of 2.8 and a threat with a score of 2.5. Based on the SWOT analysis diagram, Mitra Terang Bojonegoro Gold Shop shows in quadrant I by using an aggressive strategy, namely the company has strengths and opportunities by using strength to take advantage of existing opportunities. The strategy that can be applied is to support aggressive policy growth (growth oriented strategy) to increase sales turnover at Mitra Terang Bojonegoro Gold Shop.